Сравнение компонентного состава Pentaphylloides fruticosa (L.) O. Schwarz различных популяций - Пастух, Полина Игоревна (Перспективы развития фундаментальных наук. Т. 2 : сборник научных трудов XX Международной конференции студентов, аспирантов и молодых ученых, 25–28 апреля 2023 г.)
Extracts of Pentaphylloides fruticosa (L.) O. Schwarz were obtained. The quantitative and qualitative composition of the main and by-products was determined by the method of gas chromatography-mass spectrometry. The component composition of different samples of Pentaphylloides fruticosa (L.) O. Schwarz is compared.